The Traveling Scholar and Harbors of Urban Aesthetics - Henrik Reeh (European Journal of Creative Practices in Cities and Landscapes)
This study addresses the discovery of site-specific qualities in contemporary Venice and Marseille. Both Venice and Marseille are classic harbor cities, but their links to tourism are increasing in the age of cultural planning and consumption. Two series of results stand out. Venice proves to be site-specific at all levels of the frontstage city, as well as in the offstage of its industrious areas. Instead of rejecting the latter as alien to Venice, one should recognize the harbor zones as a reservoir of urban site-specificity. If these areas become truly public, they may in turn add a modern relief to the conventional staging of Venice. The observations of site-specificity in Marseille delve into a particular place in a critical situation: the collective bus shelter in the Vieux Port during a torrential shower. Here, sensory and reflective processes contribute to the researcher’s appreciation of site-specific qualities. Present on site, the researcher is affected by sensory impressions and socio-cultural exchanges. This reciprocity between human presence and the environment transforms urban space from cool objectivity into a matter of lived life. Critically reconsidered, such experiences may strengthen the urban-cultural reflections on site-specificity as a realm of ambiguous contributions to urban aesthetics.